The Psychodiagnostic Potential of the General Health Questionnaire and its Ukrainian-Language Adaptation - V. I. Barko; O. O. Yevdokimova; O. M. Smirnova; V. V. Barko (Bulletin of Kharkiv National University of Internal Affairs, 2025)
The article provides a comprehensive analysis of the psychodiagnostic capabilities of the foreign questionnaire on general health GHQ-28, developed in 1979 by D. Goldberg and W. Hillier. The structure of the questionnaire, based on factor analysis, includes four subscales, each of which contains seven items: somatic symptoms; anxiety; social dysfunction and severe depression. It is shown that the questionnaire is widely used abroad to determine a person’s ability to perform normal functions and diagnose certain distress-related deviations in the state of mental health.